Artificial Intelligence as a Learning Tool and Teachers as Validators: Fostering Growth Mindset in 21st-Century Classroom Learning - Mamet Mustofa; Mutiara Kartika; Surya Wahyu Hidayat; Riana Mahsar (The Indonesian Institute of Science and Technology Research, 2026)
The rapid integration of artificial intelligence (AI) into educational settings has introduced both opportunities and tensions in classroom learning. This article examines the role of AI as a learning tool and positions teachers as validators who ensure accuracy, depth, and pedagogical integrity in AI-assisted environments. Drawing on growth mindset theory, the study proposes a conceptual framework, the AI-Teacher Synergy Framework (ATSF), which delineates three interconnected phases: AI-Assisted Exploration, Teacher Validation and Feedback, and Growth Mindset Reinforcement. Through a synthesis of recent literature, the article presents findings across three dimensions: the capacity of AI to catalyze active learning, the evolving role of teachers from content deliverers to validators and mentors, and the function of growth mindset as a bridge between technology use and meaningful learning outcomes. Results indicate that AI tools increase student engagement and personalize learning pathways, but their effectiveness depends on teachers who critically evaluate AI outputs and cultivate resilience in learners. The article concludes that sustainable AI integration requires a synergistic model where technology augments instruction and teachers remain the authoritative validators of knowledge construction.